Putting the eggs in different baskets : potential marketing strategies for Icelandic Lumpfish (Cyclopterus lumpus) Roe - Burrows, John Hollis, 1991- (2018)
The Lumpfish (Cyclopterus lumpus) has been caught in Iceland for centuries. In recent decades the primary value of the lumpfish fishery in Iceland has been from the use of the roe in the creation of imitation caviar. Historically, the fishery responsible for this catch has been largely comprised of boats from rural, low-density population areas. This study looked to identify new ways to use lumpfish roe to increase their value and bring additional revenue to these smaller communities in Iceland. Due to growing consumer awareness of the benefits of long-chain n-3 polyunsaturated fatty acids (n-3 LC-PUFA’s), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), this study looked to quantify whether these acids were a marketable feature. Lumpfish roe fatty acids as percent of fatty acid methyl ester (FAME) and phospholipids (PL) as percent of total lipids (TL) were studied using gas chromatography and compared with n-3 fish/krill oil supplements currently available to consumers as well as roe of other species. Nutritional supplement data was gathered in December 2017 both online and in-person. Nutritional data were obtained from product tests and supplement labels. Lumpfish roe rated highly in n-3 content against krill oils and products made in Iceland and had a more larger proportion of n-3 than roe from other species. Compared to most finished consumer products the lumpfish roe was higher in DHA but had comparable EPA levels. Compared with roe of other species lumpfish roe was average in DHA but higher in EPA. EPA+DHA also comprised a larger percentage of n-3 than most consumer n-3 supplements of all types. Strategies to increase the value include market separation via indication of the n-3/DHA/EPA and phospholipid content and tying the product more closely with its origin with labelling. Applications which may benefit include alternative preparations, functional foods, and supplements. The nutritional properties of lumpfish roe studied herein indicate potential exists to drive the market ...